The direct effect of fibroblast growth factor 23 on vascular smooth muscle cell phenotype and function. Issue 2 (22nd July 2022) - Vergara, Noemi; de Mier, M Victoria Pendón-Ruiz; Rodelo-Haad, Cristian; Revilla-González, Gonzalo; Membrives, Cristina; Díaz-Tocados, Juan M; Martínez-Moreno, Julio M; Torralbo, Ana I; Herencia, Carmen; Rodríguez-Ortiz, María Encarnación; López-Baltanás, Rodrigo; Richards, Williams G; et al.
ABSTRACT: Background: In chronic kidney disease (CKD) patients, increased levels of fibroblast growth factor 23 (FGF23) are associated with cardiovascular mortality. The relationship between FGF23 and heart hypertrophy has been documented, however, it is not known whether FGF23 has an effect on vasculature. Vascular smooth muscle cells VSMCs may exhibit different phenotypes; our hypothesis is that FGF23 favours a switch from a contractile to synthetic phenotype that may cause vascular dysfunction. Our objective was to determine whether FGF23 may directly control a change in VSMC phenotype. Methods: This study includes in vitro, in vivo and ex vivo experiments and evaluation of patients with CKD stages 2–3 studying a relationship between FGF23 and vascular dysfunction. Results: In vitro studies show that high levels of FGF23, by acting on its specific receptor FGFR1 and Erk1/2, causes a change in the phenotype of VSMCs from contractile to synthetic. This change is mediated by a downregulation of miR-221 / 222, which augments the expression of MAP3K2 and PAK1. miR-221 / 222 transfections recovered the contractile phenotype of VSMCs. Infusion of recombinant FGF23 to rats increased vascular wall thickness, with VSMCs showing a synthetic phenotype with a reduction of miR-221 expression. Ex-vivo studies on aortic rings demonstrate also that high FGF23 increases arterial stiffening. In CKD 2–3 patients, elevation of FGF23 was associated with increased pulse wave velocity and reduced plasma levels of miR-221 / 222 . Conclusion: In VSMCs, high levels of FGF23, through the downregulation of miR-221 / 222, causes a change to a synthetic phenotype. This change in VSMCs increases arterial stiffening and impairs vascular function, which might ultimately worsen cardiovascular disease. Graphical Abstract: